Synergy Effect of Dually Superposed Orbital Angular Momentum States in Atmospheric Turbulence - Tao Zhang; Yi-Dong Liu; Jiandong Wang; Pusheng Liu; Yuanjie Yang (IEEE Photonics Journal)
We corroborate that a synergy effect may emerge when the dually superposed orbital angular momentum (OAM) states with two adjacent OAM numbers pass through a weak fluctuation regime of the atmospheric turbulence. We show that this novel effect closely depends on the transition probabilities between this two OAM eigenstates for superposition. While such probabilities become larger, the synergy effect becomes more obvious. Our examples show that the synergy effect enables OAM states to better resist phase fluctuation caused by the atmospheric turbulence.